The cartulary of the monastery of Tiron - Kathleen Thompson (Tabularia)
The cartulary of the monastery of Tiron is known to scholars from an edition published in 1883 by Lucien Merlet, archivist of the département of Eure-et-Loir. New insights about its composition and purpose have been provided by a recent re-examination of the manuscript and palaeographical analysis. The cartulary was begun before 1147 and abandoned by the 1160s. The acts are numbered and there is a 12th century contents list, suggesting that the cartulary was intended as a records management system. Originals of some of the acts survive in the Archives départementales of Eure-et-Loir and at Winchester College in England. At the beginning of the 16th century, the cartulary received its current binding and two gatherings were added, one written at that time and covering the Norman priory of Bacqueville-en-Caux, the other containing Pope Eugenius III’s confirmation and other material dating from the 12th century.